(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Intussusception is a common abdominal crisis in children, portrayed by the extending of one piece of the digestive system into another. Objectives: The main objective of the study is to find the accuracy of ultrasound in diagnosis of intussusception in children taking surgical procedures as gold standard. Material and methods: This cross-sectional research study design to evaluate the diagnostic accuracy of ultrasound in the diagnosis of intussusception in children. The study was conducted in Surgical unit of CMH/SKBZ Muzaffarabad (a tertiary care hospital) and surgical department of Ayub medical college over a period of May 2021 to May 2023. A total of 210 pediatric patients who presented with clinical signs and symptoms suggestive of intussusception were included in the study. The inclusion criteria comprised children between the ages of 3 months and 6 years who underwent ultrasound examination and subsequently received surgical intervention. Results: Data was collected from 210 patients of both male and females. The age distribution shows that the majority of participants (46.7%) fall within the age range of 1-3 years, followed by those aged 0-1 year (33.3%) and 3-6 years (20.0%). In terms of gender, the study included a slightly higher proportion of male participants (63.3%) compared to female participants (36.7%). The clinical presentation data reveals that abdominal pain was the most common symptom observed in the participants, with 53.3% reporting this symptom. Vomiting was reported by 40.0% of participants, and 13.3% presented with bloody stools. The mean age of the participants in this study is 1.85±2.34 years. Conclusion: It is concluded that ultrasound is a reliable and effective diagnostic tool in confirming or ruling out intussusception. The high sensitivity and specificity of ultrasound in detecting intussusception indicate its ability to accurately identify cases with the condition and exclude it when absent.